Validation of a questionnaire assessing school physical activity in adolescents - Gómez Campos, Rossana (2012)
Background: So far there is no questionnaire to assess the level of physical activity related to children and adolescents’ health in Peru, as well as information on measures of reproducibility. Objectives: To propose and validate a physical activity questionnaire for school adolescents living at moderate altitude. Design: Descriptive simple study. Setting: Faculty of Physical Education, UNICAMP, Brazil. Participants: School children 10 to 18 year-old. Interventions: The sample consisted of 116 students selected from a stratified probability, 58 men and 59 women, constituting 20% of National College of Immaculate Conception’s population, school located at District Jose Luis Bustamante y Rivero Arequipa (Peru). The questionnaire had 11 questions that assessed the level of physical activity using four indicators including such as activity type, frequency, duration and intensity. To determine reproducibility, test and re test procedure were done with an interval of seven days. Main outcome measures: To determine reproducibility of the questionnaire. Results: Cronbach's alpha to determine reproducibility showed high values between 0.97 and 0.98 for both sexes and a technical measurement error between 1.78 and 3.10%. Intra-class Pearson’s correlation coefficient was between 0.81 and 0.89, values that give the instrument strong reproducibility. Conclusions: The questionnaire developed to assess physical activity of public schools children had acceptable levels of validity and reliability. Results suggest its possible application to populations with similar characteristics.